The influence of a full-time, immersive simulation-based clinical placement on physiotherapy student confidence during the transition to clinical practice - Wright, A.; Moss, P.; Dennis, D.; Harrold, M.; Levy, S.; Furness, A.; Reubenson, Alan (2018)
Background: Novice students may have limited learning opportunities during their early exposure to complex clinical environments, due to the priorities of patient care. Immersive, high-fidelity simulation provides an opportunity for physiotherapy students to be exposed to relatively complex scenarios in a safe learning environment before transitioning to the clinical setting. The present study evaluated the influence of immersive simulation on student confidence and competence. Methods: Sixty penultimate year physiotherapy students completed an 18-day full-time immersive simulation placement. The placement involved students spending 6 days working in each of three core practice areas (cardiopulmonary, musculoskeletal, neurological) in which they interacted with simulated patients portrayed by professional role-play actors. The patient scenarios were developed by groups of expert practitioners and incorporated full documentary and imaging information. Students completed a questionnaire to evaluate their confidence in the clinical environment at the start and completion of each 6-day rotation. Their clinical competence was evaluated at the end of each 6-day rotation using the Assessment of Physiotherapy Practice (APP) tool. In a secondary analysis, the clinical competence of this cohort was evaluated in comparison to a matched cohort of students from the same year group that had not completed an immersive simulation placement. Results: Student confidence improved significantly in each 6-day rotation (p < 0.001); however, it reduced again at the commencement of the next rotation, and there was no cumulative improvement in confidence over the 18-day placement (p = 0.22). Students who had completed the immersive simulation placement achieved higher APP (p < 0.001) scores in an evaluation of their competence to practice during their subsequent clinical placement. Conclusion: Immersive simulation provides a beneficial learning environment to enable physiotherapy students to transition from university-based education to working in the clinical environment.